At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
The given equation is [tex]\( 9x^2 - x + 9 = 0 \)[/tex].
This equation is a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex].
To identify the coefficient [tex]\( b \)[/tex], let's match the given equation with the standard form:
1. Identify the coefficient of [tex]\( x^2 \)[/tex]:
- In the given equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex], the coefficient of [tex]\( x^2 \)[/tex] is 9. So, [tex]\( a = 9 \)[/tex].
2. Identify the coefficient of [tex]\( x \)[/tex]:
- In the given equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex], the coefficient of [tex]\( x \)[/tex] is -1. So, [tex]\( b = -1 \)[/tex].
3. Identify the constant term (the coefficient of [tex]\( x^0 \)[/tex]):
- In the given equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex], the constant term is 9. So, [tex]\( c = 9 \)[/tex].
Therefore, the coefficient [tex]\( b \)[/tex] in the equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex] is [tex]\( -1 \)[/tex].
So, [tex]\( b = -1 \)[/tex].
This equation is a quadratic equation in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex].
To identify the coefficient [tex]\( b \)[/tex], let's match the given equation with the standard form:
1. Identify the coefficient of [tex]\( x^2 \)[/tex]:
- In the given equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex], the coefficient of [tex]\( x^2 \)[/tex] is 9. So, [tex]\( a = 9 \)[/tex].
2. Identify the coefficient of [tex]\( x \)[/tex]:
- In the given equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex], the coefficient of [tex]\( x \)[/tex] is -1. So, [tex]\( b = -1 \)[/tex].
3. Identify the constant term (the coefficient of [tex]\( x^0 \)[/tex]):
- In the given equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex], the constant term is 9. So, [tex]\( c = 9 \)[/tex].
Therefore, the coefficient [tex]\( b \)[/tex] in the equation [tex]\( 9x^2 - x + 9 = 0 \)[/tex] is [tex]\( -1 \)[/tex].
So, [tex]\( b = -1 \)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.